Management Transformation of Local Government In The New Normal Era - Petrus Polyando (Journal of Governance, 2022)
This study explores the implications of adapting new habits to the administration of local government from various dimensions of government management. The main objective of this study is to show that the governance of local government in the new normal era can be productive in fulfilling the needs of the publics through changes in the administration of local government’s functions. This study places the presence of information and communication technology (ICT) as well as restrictions on social interaction in the new normal era, changing the way local government sector works. The approach departs from the main idea of adapting new habits as a conceptual framework to empirically examine changes in the dimensions of local government management which based on several factors, such as content, context, process, change outcomes and leadership. Furthermore, data collection gained through interviews with informants and data analysis are used to confirm the suitability of local government governance. The process is then carried on by formulating the concept of an ideal local government governance changes in the new normal era. The findings of the study show that local government governance system with the old paradigm is ineffective and inefficient for the fulfillment of public rights in the new normal era. For this reason, it is necessary to transform the governance of various dimensions in local government management. As originality/value, what is offered in this study is a modification of the system and working mechanism with a new paradigm for areas that are difficult geographically. This modification can be conducted in several actions, such as developing ICT applications and infrastructure; reorganizing the work system of all management dimensions that are trusted and accountable; increasing bureaucratic capacity and public knowledge; renewing the relationship between government and its people. This idea is relevant to the rapid development of the concept of adaptive governance and the strength of the role of ICT for individual and social activities.